1992
DOI: 10.1159/000294849
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Function of Granulosa Cell Tumors in vivo

Abstract: Two patients with granulosa cell tumors of the ovary, endometrial hyperplasia, elevated serum estradiol (E2) concentrations and depressed FSH levels were studied preoperatively using intravenous administration of FSH, LH and gonadotropin-releasing hormone. In patient 1 serum E2 increased from a baseline of 72.7 to 116.8 pg/ml 60 min after hCG stimulation, with a peak level of 571.4 pg/ml 96 h after hCG administration; there was a rapid postoperative decline to 16 pg/ml. Ovarian venous E Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…A preliminary study in 205 women confirmed that all of the ectopic pregnancies (nZ100) had an E 2 level !650 pg/ml and all but one of the intrauterine pregnancies had a value O650 pg/ml (Guillaume et al 1990) giving a sensitivity of 100% and specificity of 99%. However, again there was no difference in serum E 2 when women with tubal ectopic pregnancy were compared with those with nonviable intrauterine pregnancies (Witt et al 1990). There are differences in serial serum E 2 concentrations in tubal ectopic pregnancy when compared with viable intrauterine pregnancies measured up to 11 weeks of gestation (Mantzavinos et al 1991).…”
Section: Oestradiolmentioning
confidence: 88%
See 4 more Smart Citations
“…A preliminary study in 205 women confirmed that all of the ectopic pregnancies (nZ100) had an E 2 level !650 pg/ml and all but one of the intrauterine pregnancies had a value O650 pg/ml (Guillaume et al 1990) giving a sensitivity of 100% and specificity of 99%. However, again there was no difference in serum E 2 when women with tubal ectopic pregnancy were compared with those with nonviable intrauterine pregnancies (Witt et al 1990). There are differences in serial serum E 2 concentrations in tubal ectopic pregnancy when compared with viable intrauterine pregnancies measured up to 11 weeks of gestation (Mantzavinos et al 1991).…”
Section: Oestradiolmentioning
confidence: 88%
“…Guillaume et al (1990) investigated a larger population of 205 women with tubal ectopic pregnancy (nZ100), viable intrauterine pregnancy (nZ69) and threatened abortion (nZ36) and found that all but one of the women with a tubal ectopic pregnancy had serum P levels !23 ng/ml and this had a sensitivity of 99% and a specificity of 100%. However, serum progesterone levels are significantly lower in both tubal ectopic pregnancies (nZ32; P!0.001) and spontaneous abortions (P!0.001) than viable intrauterine pregnancies (Witt et al 1990). Crucially, there was no significant difference in serum progesterone concentrations in women with an ectopic pregnancy when compared with those who had a spontaneous abortion and this reduced the predictive value of progesterone.…”
Section: Progesteronementioning
confidence: 96%
See 3 more Smart Citations